UNIVERSITY EDUCATION IN THE FRENCH REPUBLIC: STRUCTURE AND LEGAL FRAMEWORK - Durdas, Alla (The Modern Higher Education Review, 2020)
The article deals with the complex and multistage system of higher education of the French Republic. The structural features of higher education in France, its complex and multi-stage system has been considered. Attention is drawn to the role of the state in the field of higher education in France. The importance of the development of education for the national development of the country and civilization as a whole has been stressed. A strong centralized presence and role of the state in the field of education in France has been noted, in particular in the organization of the educational process and in financing the education sector, as well as in determining the fundamental principles of the educational process, the details of the curriculum at all levels of education, the organization of the procedure for receiving teachers, determining the content, recruitment teachers who become public officers, ensuring their continuing education; recruiting and training inspectors responsible for quality control of the education system; funding public education and subsidizing “private schools under contract”. The article focuses on the constant attention of the state to the problems of education. It highlights the openness of the French system of higher education and its accessibility for most of the population. The features of France’s higher education management system and the specifics of its legislative framework have been disclosed. Four Legislative Acts of the Ministry of Education are characterized, played an important role in its functioning. A more democratic and collegial management of universities for today has been noted. The relevance of the study of the structure and legislative framework of university education in France has been grounded. The types of higher education institutions in France and their features in the context of development trends have been investigated. The current stage of development of the system of French university education and the features of structural transformations have been considered. The features of the functioning of universities, “grand schools” and private higher education institutions have been disclosed. The article draws attention to the achievement of the French system of higher education and its uniqueness. The role and place of large schools in the system of higher education in France have been highlighted. Leading elite schools and universities have been mentioned, as well as the conditions for entering them. Attention was paid to the almost equal quality of education in the capital and in the province.